Bipartite consensus tracking problem of networked Lagrangian system with intermittent interactions. Issue 13 (September 2022) - Zhang, Qiu-Yue; Ge, Ming-Feng; Liang, Chang-Duo; Ding, Teng-Fei; Park, Ju H.
Abstract: This paper studies the bipartite consensus tracking (BCT) problem of the networked Lagrangian system (NLS) with intermittent interactions, in which the interaction among the individuals is on in the interactive time intervals and is off in the un-interactive ones. Besides, different from the existing works, where the dynamics of the system is linear or nonlinear, we consider the Lagrangian system in this paper with dynamical characteristics: high nonlinearity and coupling. In such case, a hierarchical intermittent-interactions-based control (HIIC) algorithm, including the distributed intermittent estimator and local control algorithm, is designed to achieve the above-mentioned control goal. Specifically, the distributed intermittent estimator is constructed to estimate the information of the leader for each individual. The local control algorithm is designed based on the derived estimators to address the BCT problem finally. Furthermore, the sufficient conditions for ensuring the stability of the closed-loop system are derived through systematic Lyapunov stability analysis. Finally, some numerical simulations on the networked manipulators are performed to prove the validity of the proposed HIIC algorithm.